Defect inspection of flip chip solder joints based on non-destructive methods: A review. (July 2020) - Su, Lei; Yu, Xiaonan; Li, Ke; Pecht, Michael
Abstract: Flip chip technology has been widely used in integrated circuit packages due to its superiority of performance in various aspects. The solder joints sandwiched between chips and organic substrates, act as the mechanical and electrical connections in flip chips. However, with the trend of flip chips towards ultra-fine pitch and high density, and the new requirements of encapsulation materials, the solder joints are more likely to suffer from the defects of cracks, voids, balls missing. These defects affect the performance and service life of flip chips and result in false alarms. Solder joint defects can be detected using both contact and non-contact ways, and non-contact testing methods have proven to be more successful than contact methods for detecting the solder joint defects. This review emphasizes the main results of research in the field of solder joints defect inspection approaches and clarifies the principle of the methods as well as the corresponding advantages and disadvantages.